2010
DOI: 10.1177/1534735409360361
|View full text |Cite
|
Sign up to set email alerts
|

Chemoprotective Effects of Zataria multiflora Against Genotoxicity Induced by Cyclophosphamide in Mice Bone Marrow Cells

Abstract: The preventive effective of Zataria multiflora (ZM) extract was investigated in mouse bone marrow cells against genotoxicity induced by cyclophosphamide (CP). Mice were orally (gavaged) pretreated with solutions of ZM extract prepared at 3 different doses (50, 100, and 200 mg/kg body weight) for 7 consecutive days. They were injected with CP (50 mg/kg body weight) on the seventh day of treatment and killed after 24 hours for the evaluation of micronucleated polychromatic erythrocytes (MnPCEs) and the ratio of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 18 publications
2
28
0
Order By: Relevance
“…The cellular and tissues toxicity were observed in the increased therapeutic dose of CP. We previously reported CP-induced oxidative stress and genotoxicity in mice bone marrow cells [22, 23]. We previously reported that CP increased the TBARS levels and therefore the extent of lipid peroxidation in the testis tissue of the experimental animals [24].…”
Section: Discussionmentioning
confidence: 99%
“…The cellular and tissues toxicity were observed in the increased therapeutic dose of CP. We previously reported CP-induced oxidative stress and genotoxicity in mice bone marrow cells [22, 23]. We previously reported that CP increased the TBARS levels and therefore the extent of lipid peroxidation in the testis tissue of the experimental animals [24].…”
Section: Discussionmentioning
confidence: 99%
“…Concentration-dependent effects of the extract also confirm anti-inflammatory effects of Z. multiflora . The effects of the three concentrations of the extract were studied according to the previous studies [36–41] and, using these concentrations, a plateau in the effect of the extract was not achieved.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the effect of the extract on other cytokines, inflammatory mediators, and biomarkers such as ED-1 should be examined in further studies. In the present study, the effects of only three concentrations of the extract were examined which were chosen based on the previous studies [36–41] which were insufficient for determination of IC50 for extracts and its effective dose. Therefore, IC50 for extracts and its effective dose should be examined in further studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…23,24 The bone marrow Mn test is a well-known in vivo assay for the assessment of genotoxicity in animals such as mice and rats. All groups treated with CP had the drug injected intraperitoneally, 25 while three type of honey was administered by Oral Intubation (O.I.)…”
Section: Mn Assaymentioning
confidence: 99%